Role of thymectomy in myasthenia gravis - Shweta Shende; Sushrut Potwar; Kanak Nagle; Pankaj Pohekar; Rahul Nathani; Hari Nair (International Journal of Medical Research and Review, 2016)
Aims and Objective: The aim of study is to show the effect of thymectomy with symptomatic improvement in patients and decrease in dose of medication requirement. To study the outcome of patients with respect to histology, duration of symptoms, remission of symptoms and post operative outcome.Methods: We prospectively analysed 28 patients with symptoms of myasthenia gravis with respect to patients profile, patients remission of symptoms with respect to age, and grade of disease, the response to thymectomy with respect to histology, and duration of symptoms.Result and Conclusion: Patients mainly present with easy fatigability, patients with mild disease respond well to surgery, hyperplasia is favorable histology for remission and lesser the duration of symptoms more are the chances of remission of disease.